Novel Ni–Co-based superalloys with high thermal stability and specific yield stress discovered by directed energy deposition - Boryung Yoo; Chanwon Jung; Kyuseon Jang; Hosun Jun; Pyuck-Pa Choi (Materials & Design, 2024)
We report on the rapid alloy screening of Ni–Co–Ti–Al–Mo superalloys with high thermal stability and specific yield stress by means of directed energy deposition. A laser directed energy deposition, a specific type of additive manufacturing, was employed using multiple powder feeders and elemental powders. Fifty superalloys of different compositions were deposited and the heat-treated microstructure and γ' solvus temperature were examined. The 43Ni–38Co–9Ti–6Al–4Mo superalloy (atomic percent composition) exhibited a uniform γ/γ' microstructure and a γ' solvus temperature of 1202°C. The beneficial properties of the superalloy were also found in the cast superalloy of identical composition. The cast superalloy exhibited a thermally stable γ/γ' microstructure with cuboidal γ' precipitates even after long-term aging heat treatments at 800°C, 900°C, and 1000°C up to 500 h. The γ'-coarsening mechanism was evaluated based on the Lifshitz–Slyozov–Wagner model and the trans-interface diffusion-controlled model. A transition between these two mechanisms was observed with an increase in aging temperature. Atom probe tomography analyses revealed that the sluggish interface diffusion of Co and corresponding reduction of the interfacial energy induced the transition of the γ'-coarsening mechanism. Moreover, the cast superalloy showed an enhanced specific yield stress attributed to its exceptionally low alloy density of 7.61 g/cm3.